MANAJEMEN HUBUNGAN MASYARAKAT SEKOLAH DALAM PEMBENTUKAN CITRA POSITIF DI SMK TUNAS HARAPAN PATI - Amanda Putri Paradilla; Muhamad Nukha Murtadlo (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze public relations management in shaping a positive image at SMK Tunas Harapan Pati, which includes planning, implementation, evaluation, and school communication strategies. This study was conducted using a qualitative approach with data collection techniques through interviews, observation, and documentation. The informants in this study consisted of the principal, the vice principal in charge of public relations, and parents of students. The validity of the data was strengthened through source triangulation and method triangulation to ensure that the research results were more accurate and reliable. The results of the study show that public relations management is carried out in a structured manner through programs such as Field Work Practice (PKL), competency tests, human resource development, and partnerships with the business world and industry. The implementation of activities is supported by the use of digital media and direct communication with the community. Evaluations are carried out periodically through the ISO 9001:2015 quality management system as a basis for continuous improvement. This strategy has resulted in increased public trust and high enrollment interest every year.